Should we care? The economic effects of financial sanctions on the Russian economy - Anna Pestova; Mikhail Mamonov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
We employ a Bayesian VAR model to estimate the economic effects on the Russian economy from Western financial sanctions imposed in 2014. Sanctions caused a decrease in the amount of out-standing Russian corporate external debt, but it occurred during an episode of falling oil prices. We disentangle the effects of sanctions and oil prices by computing out-of-sample projections of key Russian macroeconomic variables conditioned solely on the oil price drop and on both the oil price drop and external debt deleveraging. Declining oil prices alone do not explain the depth of economic crisis in Russia, but we get rather accurate conditional forecasts when the actual path of external debt deleveraging is added. We treat the difference between these two projections as the effect of sanctions against Russia. The effect is modest, yet significant, for most of the variables discussed. While our estimate of the impact of sanctions on GDP growth has large uncertainty, over two-thirds of the density lies in the negative area.
URN:NBN:fi:bof-201907291308
Keywords: C51; E37; E44; F34; 330; financial sanctions; conditional macroeconomic forecasting; oil prices; corporate external debt; Bayesian VAR